2020
DOI: 10.1042/bsr20200352
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative systemic immune-inflammation index predicts prognosis and guides clinical treatment in patients with non-small cell lung cancer

Abstract: Objectives: The purpose of the present study was to evaluate the prognostic value of a systemic immune-inflammation index (SII) and the relationship between SII and the effectiveness of postoperative treatment in patients with non-small cell lung cancer (NSCLC). Methods: A total of 538 patients diagnosed with NSCLC who had undergone curative surgery were retrospectively enrolled in the study. Clinicopathologic and laboratory variables were collected. SII was defined as neutrophil × platelet/lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“…Meanwhile, LMR and PLR at post-treatment in the third period seemed to have a more balanced prediction probability for ESCC patients who had responded or no response; thus, there was a more ideal prediction probability in combining LMR with PLR at post-treatment in the third period. Prior studies reported that SII at baseline might predict pCR status for neoadjuvant chemoradiotherapy in patients with locally advanced rectal cancer [ 33 ], and non-small cell lung cancer patients with preoperative high SII levels benefit from adjuvant chemotherapy [ 34 ], which suggests a certain degree of consistency with our results. However, we attempted to combine these inflammation indices to determine whether they could predict the efficacy, instead of using a single or dual biomarkers.…”
Section: Discussionsupporting
confidence: 84%
“…Meanwhile, LMR and PLR at post-treatment in the third period seemed to have a more balanced prediction probability for ESCC patients who had responded or no response; thus, there was a more ideal prediction probability in combining LMR with PLR at post-treatment in the third period. Prior studies reported that SII at baseline might predict pCR status for neoadjuvant chemoradiotherapy in patients with locally advanced rectal cancer [ 33 ], and non-small cell lung cancer patients with preoperative high SII levels benefit from adjuvant chemotherapy [ 34 ], which suggests a certain degree of consistency with our results. However, we attempted to combine these inflammation indices to determine whether they could predict the efficacy, instead of using a single or dual biomarkers.…”
Section: Discussionsupporting
confidence: 84%
“…A total of 23 studies comprising 8361 lung cancer patients were included. 7 - 10 , 12 - 30 Among these patients, 5702 (68%) were males, 4548 were current smokers and 2212 were diagnosed with squamous carcinoma. The main features of the included studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“… 19 All selected studies analyzed the association between OS and pretreatment LMR. Thirteen studies reported PFS, 5 studies evaluated RR, 17 , 20 , 24 , 26 5 studies evaluated disease-free survival(DFS), 12 , 13 , 19 , 21 , 23 and 1 study analyzed recurrence-free survival (RFS). 16 Chemotherapy, EGFR-TKIs, stereotactic ablative radiotherapy (SABR), chemotherapy plus TKI treatment, chemotherapy plus radiotherapy and surgery were used to treat lung cancer patients in the different studies.…”
Section: Resultsmentioning
confidence: 99%
“…An unspecified level of bias also may have been introduced by modeling missing values, although such bias is generally believed to be less than the bias incurred by deleting these data points. In our analysis, we used the median as the cutoff value for SII, given that there is no established uniform cutoff value in literature for this marker [78]. In future studies, a consensus optimal cutoff value for SII should be determined from population-based studies, using appropriate statistical methods to adjust for multiplicity.…”
Section: Discussionmentioning
confidence: 99%